The damped sloshing in an upright circular tank due to an orbital forcing - Timokha, A.N.; Raynovskyy, I.A. (Доповіді НАН України, 2017)
The nonlinear Narimanov—Moiseev-type modal system with linear damping terms is employed to study the damped steady-state resonant sloshing in an upright circular tank due to a prescribed horizontal orbital (elliptic) tank motion with the forcing frequency close to the lowest natural sloshing frequency. Whereas the undamped sloshing implies coexisting the co-directed (with forcing) and counter-directed angular progressive waves (swirling), the damping makes the counter-directed swirling impossible as the forcing orbit tends to a circle.